AI-DRIVEN SECURITY ASSURANCE: TRANSFORMING MODERN CYBERSECURITY OPERATIONS - Sachin Kediyal (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
This comprehensive article explores the transformative impact of Artificial Intelligence on modern cybersecurity operations and security assurance practices. The article examines how AI integration has revolutionized various security aspects, including threat detection, code security, automated testing, vulnerability management, and future security practices. The article delves into how AI-driven solutions have enhanced operational efficiency while addressing complex security challenges across organizations. The article analyzes the evolution of security practices through AI implementation, covering areas such as automated attack path analysis, real-time threat intelligence integration, behavioral analysis, and predictive risk assessment. It further examines the improvements in code security practices, including static analysis capabilities, vulnerability detection, and false positive reduction. The article also evaluates the advancements in security testing, monitoring systems, and smart vulnerability management, highlighting how AI has transformed traditional security approaches. Additionally, the article explores the future landscape of AI security assurance, discussing compliance integration, implementation challenges, and the overall impact on security teams and practices.